Determinants of the Moka POS Adoption by Micro, Small, and Medium Enterprises in Jakarta Using Unified Theory of Acceptance and Use of Technology Model - Devana Ayu Nurcholisha; Jurica Lucyanda (Journal of International Conference Proceedings (JICP), 2022)
The purpose of this study is to examine the behavioral intention/actual behavior of adoption of Mobile Kasir Point of Sale (Moka POS) users using Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Micro, Small, and Medium Enterprises (MSME) have a major contribution to the Indonesian economy, especially MSMEs in Jakarta as an economic center of the nation. During the pandemic, MSMEs are increasingly aggressive in optimizing the use of digital technology in accounting such as Moka POS. The research method is a survey using electronics questionnaires to MSME owners in Jakarta who are using Moka POS. The data analysis technique used a Structural Equation Model (SEM) with the Smart Partial Least Square (PLS) software approach. The result shows that performance expectancy, effort expectancy, and social influence have a positive effect on behavioral intention, and behavioral intention also has a positive effect on actual behavior to use the Moka POS. Meanwhile, facilitating conditions did not positively affect actual behavior to use the Moka POS. This study contributed theoretical and practical contributions to behavioral accounting. Keywords: Micro, Small, and Medium Enterprises, Moka POS, Unified Theory of Acceptance and Use of Technology.